(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sefrila M, Ghulamahdi M, Purwono Melati M, Mansur I. 2021. Diversity and abundance of arbuscular fungi mycorrhizal (AMF) in rhizosphere Zea mays in tidal swamp. Biodiversitas 22: 5071-5076. This study aims to find out the diversity and dominance of AMF spores and look at the morphology of fungi mycorrhizal arbuscular fungi that exist in the rooting area of corn (Zea mays L.) crops in the tidal swamp. The study was conducted in September 2020. Soil sampling at the tidal swamp village of Mulyasari Tanjung Lago District, Banyuasin, South Sumatra, Indonesia randomly sampling the corn root zone method. The research stages are soil sampling, soil chemistry analysis, AMF isolation and trapping, and morphological identification of AMF spores. The results showed the number of spores found in soil samples in the corn crop rhizosphere before trapping was less when compared to after trapping. The spores’ shape is round, oblong, and oval, with colors ranging from clear, yellow, to brown. AMF spores found come from 2 genera namely (Acaulospora scrobiculata, A. bireticulata, A. mellea, A. laevis) and Glomus (Glomus monosporum, G. constrictum, G. manihotis).